2014
DOI: 10.1038/srep05905
|View full text |Cite
|
Sign up to set email alerts
|

Type 2C Protein Phosphatase Is a Key Regulator of Antiviral Extreme Resistance Limiting Virus Spread

Abstract: Effector-triggered immunity (ETI) is an active immune response triggered by interactions between host resistance proteins and their cognate effectors. Although ETI is often associated with the hypersensitive response (HR), various R genes mediate an HR-independent process known as extreme resistance (ER). In the soybean-Soybean mosaic virus (SMV) pathosystem, the strain-specific CI protein of SMV functions as an effector of Rsv3-mediated ER. In this study, we used the soybean (Rsv3)-SMV (CI) pathosystem to gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(90 citation statements)
references
References 47 publications
(95 reference statements)
4
86
0
Order By: Relevance
“…Rsv3 ‐mediated resistance to SMV is not accompanied by obvious symptoms, and it has been referred to as ER (Fig. B) (Seo et al ., ). However, using a GUS‐tagged SMV strain, Zhang et al .…”
Section: Signalling and Host Responsesmentioning
confidence: 97%
“…Rsv3 ‐mediated resistance to SMV is not accompanied by obvious symptoms, and it has been referred to as ER (Fig. B) (Seo et al ., ). However, using a GUS‐tagged SMV strain, Zhang et al .…”
Section: Signalling and Host Responsesmentioning
confidence: 97%
“…Recently, it has been shown that silencing GmHSP40.1 , a soybean nuclear-localized type-III DnaJ domain-containing HSP40, results in increased infectivity of SMV, indicating a positive role of GmHSP40.1 in basal resistance (Liu and Whitham, 2013). A subset of type 2C protein phophatase (PP2C) gene family, which participate ABA signaling pathway, is specifically up-regulated during Rsv3 -mediated resistance (Seo et al, 2014). Synchronized overexpression of GmPP2C3a using SMV-G7H vector inhibits virus cell-to-cell movement mediated by callose deposition in an ABA signaling-dependent manner, indicating that GmPP2C3a functions as a key regulator of Rsv3 -mediated resistance (Seo et al, 2014).…”
Section: The Host Factors That Are Involved In Smv Resistancementioning
confidence: 99%
“…A subset of type 2C protein phophatase (PP2C) gene family, which participate ABA signaling pathway, is specifically up-regulated during Rsv3 -mediated resistance (Seo et al, 2014). Synchronized overexpression of GmPP2C3a using SMV-G7H vector inhibits virus cell-to-cell movement mediated by callose deposition in an ABA signaling-dependent manner, indicating that GmPP2C3a functions as a key regulator of Rsv3 -mediated resistance (Seo et al, 2014). An ortholog of Arabidopsis K + weak channel encoding gene AKT2, was significantly induced by SMV inoculation in the SMV highly resistant genotype, but not in the susceptible genotype (Zhou et al, 2014).…”
Section: The Host Factors That Are Involved In Smv Resistancementioning
confidence: 99%
“…Using transcriptomics to study soybean-Soybean mosaic virus (SMV) pathosystem Seo et al (2014) identified a 2C protein phosphatase type gene (PP2C) as a key regulator of ER, confirming transcriptomics as a valuable approach. Baebler et al (2009) detected differences in expression of hundreds of genes as soon as half an hour after inoculation of potato leaves with PVY NTN .…”
Section: Effects Of Viruses On Potato Gene Expressionmentioning
confidence: 98%
“…Three mechanisms whereby the NIa could act were proposed: [1] the structure of the NIa might have elicitor activity, [2] the elicitor might be produced by degradation of a host-encoded protein by NIa, [3] the NIa might degrade a negative regulator of the resistance (Mestre et al, 2000). The role of callose deposition in inhibition of viral cell-to-cell movement by R-mediated ER has also been reported in soybean-SMV pathosystem (Seo et al, 2014).…”
Section: Genes Associated With Er Type Resistancementioning
confidence: 99%